PENILAIAN TINGKAT KINERJA KEUANGAN DENGAN METODE ANALISIS DU PONT SYSTEM PADA PT TELKOM INDONESIA (PERSERO) TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017–2021 - Kevin Evert Richarson Lobo; Wehelmina M Ndoen; Hironnymus Jati (Universitas Nusa Cendana, 2022)
This study aims to determine the level of financial performance using the Du Pont System analysis method at PT Telkom Indonesia (Persero) Tbk which is listed on the Indonesia Stock Exchange for the period 2017–2021. The type of research is descriptive research, with a quantitative research approach. The variables included Net Profit Margin, Total Asset Turn Over, Return on Investment, Equity Multiplier, Return on Equity. The type of data is quantitative, namely the financial statements of PT Telkom Indonesia (Persero) Tbk, with secondary data sources. Data collection techniques is documentation and data analysis technique is quantitative descriptive. Results obtained that the assessment of the level of financial performance, which are the ratio of Total Asset Turn Over, Return on Invesment, Equity Multiplier, Return on Equity, is in the category of poor performance. Keywords: Du Pont System, Net Profit Margin, Total Asset Turn Over, Return on Invesment, Equity Multiplier, Return on Equity